Comparison of induction of labor methods for unfavorable cervices in trial of labor after cesarean delivery. (3rd May 2017) - Shah, Utsavi; Bellows, Patricia; Drexler, Kathleen; Hawley, Lauren; Davidson, Christina; Sangi-Haghpeykar, Haleh; Gandhi, Manisha
Abstract: Objective : To compare induction of labor methods in patients attempting a trial of labor after cesarean (TOLAC) with an unfavorable cervix. Methods : This is a retrospective cohort study from patients attempting TOLAC from 2009 to 2013. Patients with a simplified Bishop score of three or less where labor was initiated with either a Cook balloon or oxytocin were included. Our primary outcome was mode of delivery. Our secondary outcomes included duration of labor and multiple maternal and neonatal morbidities. Results : Two-hundred and fourteen women met inclusion criteria: 150 received oxytocin and 64 had the Cook balloon placed. The vaginal birth after cesarean delivery rate was significantly higher in the oxytocin group at 70.7% versus 50.0% in the Cook balloon group ( p = 0.004). In the multivariable analysis, odds for cesarean delivery were two times higher with the Cook balloon than with oxytocin (Adjusted OR = 2.09, 95% CI = 1.05-4.18, p = 0.036). The duration of labor was longer with the Cook balloon versus oxytocin (21.9 versus 16.3 hours, p = 0.0002). There were no significant differences in maternal and neonatal health outcomes. Conclusion : Oxytocin induction of labor was associated with a higher rate of vaginal delivery and a shorter duration of labor compared to the Cook balloon in women undergoing TOLAC with an unfavorable cervix.